To Defeat Pain: The Lightness of the Posthumanist Dream - Torre Díaz, Francisco Javier de la (Concilium, 2025)
This article describes the diverse physical, psychological and social dimensions of pain, the difficulty of separating it from suffering, and the importance to contemporary science of diminishing it. It presents the ideas of contemporary trans-humanist and post-humanist movements, and their recent project of defeating pain. The article concludes by re-examining the fundamental criticisms of the posthuman and transhuman approach to creating a life without pain.